Педагогічний аспект професійної підготовки фахівців з безпеки трудової діяльності - Демідова, Юлія Євгенівна; Мовмига, Наталія Євгенівна (Полтавська академія неперервної освіти імені М. В.Остроградського, 2023)
Розглянуто основні напрями розвитку ключових компетенцій сучасних фахівців з безпеки праці. Особливо важливого значення набуває формування знань у сфері розвитку компетенцій із професійної безпеки. Для вдосконалення професійного розвитку необхідно розширювати межі знань і вмінь орієнтовно на результат навчання з позицій удосконалення професійних компетенцій. Поняття професійної компетентності виражає єдність його теоретичної та практичної готовності у цілісній структурі особистості й характеризує його професіоналізм. Проблема формування професійних компетенцій останніми роками набуває великого значення. Це пов’язано з інтенсифікацією професійної діяльності, необхідністю вирішення професійних завдань в умовах невизначеності, ризику, появою та розвитком нових технологій.

The modern education system must quickly adapt to the needs of the economy and provide occupational safety specialists with quality knowledge that will enable them to become competitive specialists. The result of today’s training is the ability to adapt to new conditions and the readiness to solve complex tasks at the intersection of filds of knowledge. The traditional model of education establishes artifiial disciplinary boundaries, limiting the development of knowledge and skills in only one direction. The complexity of the occupational safety specialist’s professional activity is manifested in the variety of components and relationships between them and the external environment. To improve professional development, it is necessary to expand the boundaries of knowledge, abilities, and skills based on the goal and result of training from the standpoint of improving professional competencies. The concept of the specialist’s professional competence expresses the unity of his theoretical and practical readiness in the integral structure of the individual and characterizes his professionalism. The problem of the formation of professional competences of specialists in higher education has gained great importance in recent years. This is related to the intensifiation of professional activity, the need to solve professional tasks in conditions of uncertainty and risk, and the emergence and development of new industrial and information technologies. Professional activity becomes more complicated. Changes in the conditions of labor activity, for which the biological reconstruction of the human body does not keep up, lead to the emergence of a whole bottom of negative phenomena. Sometimes working at the limit of psychophysiological capabilities and in an unfavorable production environment, a person makes mistakes. Therefore, there is a need to study the professional environment and activities of a specialist in a single complex, considering the optimal working conditions of the specialist and his psychophysiological capabilities and features.
Pedagogical aspect of professional training of occupational safety specialists
Keywords: професійна компетентність; безпека праці; фахівець; діяльність; professional competence; occupational safety; specialist; activity